2015
DOI: 10.5194/hess-19-1677-2015
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of the impact of climate and land use changes on groundwater quantity and quality in the Mancha Oriental system (Spain)

Abstract: Abstract. Climate and land use change (global change) impacts on groundwater systems cannot be studied in isolation. Land use and land cover (LULC) changes have a great impact on the water cycle and contaminant production and transport. Groundwater flow and storage are changing in response not only to climatic changes but also to human impacts on land uses and demands, which will alter the hydrologic cycle and subsequently impact the quantity and quality of regional water systems. Predicting groundwater rechar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…Most of the global and regional climate models predict an increase in 10.1002/2017EF000545 temperature, and a decrease in precipitation, with a general increase of variability [AEMET, 2008]. Analyses of the effect of climate change on future water resources forecast important reductions in hydrological inflows to rivers [Chirivella Osma et al, 2015] and groundwater recharge [Pulido-Velazquez et al, 2015], resulting in an overall decrease of water availability and more frequent and more intense drought episodes [Hernández-Barrios, 2007;CEDEX, 2010;Escriva-Bou et al, 2017]. These climate change-related impacts have severe social and economic implications, and create further hydrological problems like the rise of salinity in coastal aquifers and increased water quality problems.…”
Section: 1002/2017ef000545mentioning
confidence: 99%
“…Most of the global and regional climate models predict an increase in 10.1002/2017EF000545 temperature, and a decrease in precipitation, with a general increase of variability [AEMET, 2008]. Analyses of the effect of climate change on future water resources forecast important reductions in hydrological inflows to rivers [Chirivella Osma et al, 2015] and groundwater recharge [Pulido-Velazquez et al, 2015], resulting in an overall decrease of water availability and more frequent and more intense drought episodes [Hernández-Barrios, 2007;CEDEX, 2010;Escriva-Bou et al, 2017]. These climate change-related impacts have severe social and economic implications, and create further hydrological problems like the rise of salinity in coastal aquifers and increased water quality problems.…”
Section: 1002/2017ef000545mentioning
confidence: 99%
“…Climate change projections for the Iberian Peninsula indicate a decreasing trend in annual mean rainfall and an increase in heavy rainfalls [9,10], although there are divergences depending on the model and the greenhouse gas emission scenario used. The impact of the expected climate change on river regimes in the Iberian Peninsula has been estimated by several scientists [11][12][13][14][15][16], but the impact of changes on soil erosion and sediment yield at catchment scale has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Although we acknowledge the robustness that an adjustment of the irrigation strategies could bring to climate change scenarios (Zhao et al, 2015), we decided to have a conservative assumption (i.e., unchanged irrigation) due to large uncertainties (Wada et al, 2013) associated with choosing a specific irrigation adjustment (Klove et al, 2014). Indeed, for this region (the Ebro region), there have been many studies that have shown large variation in the range (3-20%) of irrigation need predictions (Iglesias and Minguez, 1997;Jorge and Ferreres, 2001;Döll, 2002;Fischer et al, 2007;Rey et al, 2011;von Gunten et al, 2015).The large uncertainty in these estimates is not only due to climate models and scenarios used (García-Vera, 2013), but also to factors in relation with future human impacts on land use changes and demands (Pulido-Velazquez et al, 2015). For example, the future choice of crop types by farmers as a response to climatic change or social and economic factors (von Gunten et al, 2015) is likely to play an important role in constraining future irrigation water demand (Wada et al, 2013).…”
Section: Model Running and Parametrizationmentioning
confidence: 99%